(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To study the results of using balloon sinusplasty in the treatment of chronic rhinosinusitis. Subjects and methods: All articles worldwide on the use of balloon sinusplasty in the treatment of chronic rhinosinusitis from 2005 to 2026. Methods: Scoping review using the PRISMA-ScR checklist, updated to April 2026. Results: Eleven studies involving 695 patients were included. Studies originated from Asia (45.5%), Europe (27.3%), and the Americas (27.3%), predominantly using prospective interventional designs without control groups (36.4%). BSP demonstrated clinically significant symptom improvement, with SNOT-22 score reductions ranging from 17.6 to 43 points and SNOT-20 reductions from 1.57 to 2.5 points. Success rates ranged from 62% to 96.7%. Complications were mostly mild with no serious adverse events reported. Recurrence rates ranged from 1.3% to 22% depending on follow-up duration. Conclusion: Balloon sinus dilation is an effective and safe method for treating mild to moderate chronic rhinosinusitis and may be considered as an option in some cases before endoscopic sinus surgery